A Primer for Competing Successfully in Emerging Markets. (May 2015) - Merchant, Hemant
This study empirically identifies three strategies for creating shareholder value for firms who venture into emerging markets (EMs) in search of corporate growth and profitability. Our findings demonstrate how firms can—and do—tap into the potential that EMs offer, despite the inherent risks of these markets and/or constraints on corporate resources. Statistically, no single shareholder value-creating strategy is more (or less) remunerative than other strategies. Many equally profitable trajectories coexist vis-à-vis corporate growth in EMs. The principles we have isolated have a broad appeal because they identify variety of paths that facilitate shareholder value creation via participation in joint ventures based in EMs. We expose the inner workings of these trajectories and illustrate particular firm-specific and location-specific combinations associated with profitable EM ventures. This study seriously challenges the conventional view that value creation is a function of singular positive influences. On the contrary, this study establishes that value creation is multidimensional and submits that a more refined way to augment performance is to develop an ability to combine relevant firm-specific and location-specific factors so that they can, if needed, offset the impositions of each other.